2018
DOI: 10.1016/j.bpsc.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Between Anterior Insula and Key Nodes of Frontoparietal Executive Control and Salience Networks Distinguish Bipolar Depression From Unipolar Depression and Healthy Control Subjects

Abstract: Impaired functional connectivity between the anterior insula and the inferior parietal lobule of the ECN distinguishes patients with bipolar depression from those with unipolar depression and healthy control subjects. This finding highlights a pathophysiological mechanism with potential as a therapeutic target and a clinical biomarker for bipolar disorder, exhibiting reasonable sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 70 publications
(65 reference statements)
6
47
2
Order By: Relevance
“…Our finding showed increased FC between right AI and several specific brain regions, including the middle temporal gyrus and angular, which are known as nodes of the default network (DMN). These findings are consistent with previous studies of aberrant FC in BD (33)(34)(35). Ellard et al (33) observed that compared to patients with unipolar depression and HCs, BD patients showed significantly aberrant FC between right AI and the IPL in DMN.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding showed increased FC between right AI and several specific brain regions, including the middle temporal gyrus and angular, which are known as nodes of the default network (DMN). These findings are consistent with previous studies of aberrant FC in BD (33)(34)(35). Ellard et al (33) observed that compared to patients with unipolar depression and HCs, BD patients showed significantly aberrant FC between right AI and the IPL in DMN.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies of aberrant FC in BD (33)(34)(35). Ellard et al (33) observed that compared to patients with unipolar depression and HCs, BD patients showed significantly aberrant FC between right AI and the IPL in DMN. The DMN might involve in self-referential mental process and social cognition (29,31,36,37).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In human imaging studies, the dorsal ACC (dACC) responds to relevant environmental stimuli ( Seeley et al, 2007 ; Uddin, 2015 ). The anterior insula (aINS) co-activates along with the dACC to generate, along with other structures, the so-called salience network of brain regions ( Taylor et al, 2009 ; Cai et al, 2014 ; Uddin, 2015 ; Ellard et al, 2018 ). In the rhesus monkey, the ACC and aINS are connected only by large Von Economo neurons (VENs) found in both dACC and aINS ( Mesulam and Mufson, 1982 ).…”
Section: Discussionmentioning
confidence: 99%